RETRACTED: Antibacterial Activity Test Combination of Kencur (Kaempferia galanga L) Rhizome and Sapodilla (Manilkara zapota L) Leaf Extract against Escherichia coli - Amanda Fadilah Ilhani; Ismedsyah Ismedsyah (Borneo Journal of Pharmacy, 2018)
This article has been retracted as a result of multiple publications from the article by the relevant author. Similar articles can be found at the URL https://ejurnal.stmik-budidarma.ac.id/index.php/pelita/article/view/892